MENINGKATAN HASIL BELAJAR SISWA MENULIS LEPAS DENGAN MENGGUNAKAN MEDIA BUKU TULIS HALUS PADA KELAS I SDN 04 PADANG GANTING - MASYURYANI MASYURYANI (STKIP Pesisir Selatan, 2019)
Freelance writing is a skill found in four aspects of Indonesian language learning by combining letters by letters, so as to form words and sentences. Freelance writing requires patience and perseverance when doing it. This type of research is (Classrom Action Research). The subjects of this study were students of grade I SDN 04 Padang Ganting, accompanied by one of the senior teachers as peers or supervisor / observer. From the results of preliminary observations, it shows that almost all grade 1 students at SDN 04 Padang Ganting have not been able to write off properly. But after applying the use of examples and media of fine writing as well as providing motivation per cycle, shows that student learning activities which were originally 56.5% in cycle 1 increased to 86.96% in cycle 2. This means that through the use of examples and media of fine writing skills freelance writing for SDN 04 Padang Ganting students experienced a significant increase in the 2018/2019 school year.